2023
DOI: 10.7759/cureus.37174
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis Patients Treated With Methotrexate Have an Increased Risk of Nonmelanoma Skin Cancer: A Systematic Review and Meta-Analysis

Abstract: Both psoriasis and methotrexate are associated with an increased risk of nonmelanoma skin cancer. The effect of methotrexate on the development of nonmelanoma skin cancer in patients with psoriasis is currently unknown. To evaluate this relationship, a systematic review of the literature was conducted using databases including Ovid Medline (from 1946), Scopus (from 1970), and Embase (from 1974) through June 2019. Observational comparative and case-control studies comparing psoriasis patients treated with metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Methotrexate (MTX) is an antifolate therapy, most commonly used in the treatment of rheumatoid arthritis (RA) [ 57 ], psoriasis [ 58 ], inflammatory bowel disease, and a variety of cancers, including lung, breast, and leukemia. The primary mechanism of action involves the inhibition of dihydrofolate reductase (DHFR) which is involved in purine and pyrimidine synthesis [ 57 ], the building blocks for DNA and RNA.…”
Section: Chemotherapy-induced Kidney Injurymentioning
confidence: 99%
“…Methotrexate (MTX) is an antifolate therapy, most commonly used in the treatment of rheumatoid arthritis (RA) [ 57 ], psoriasis [ 58 ], inflammatory bowel disease, and a variety of cancers, including lung, breast, and leukemia. The primary mechanism of action involves the inhibition of dihydrofolate reductase (DHFR) which is involved in purine and pyrimidine synthesis [ 57 ], the building blocks for DNA and RNA.…”
Section: Chemotherapy-induced Kidney Injurymentioning
confidence: 99%
“…It should be noted that haemodialysis does not address the underlying disease but instead prolongs life and allows for the progression of multiple systemic conditions. 3 The choice between PD and HD is crucial for patient outcomes. Studies on survival rates show mixed results, initially favouring PD due to residual renal function (RRF), but as RRF declines, there are potential risks.…”
mentioning
confidence: 99%
“…In recently published studies, researchers have concluded that the use of this drug in psoriatic patients might be doing more harm than good. In a meta-analysis performed by Margaret et al, It was found that psoriasis patients receiving MTX therapy have a 2.8-fold greater likelihood of developing nonmelanoma skin cancer (NMSC) in comparison to those who do not undergo MTX treatment 3 . Moreover, there is evidence that prolonged use of MTX may be associated with an increased probability of developing basal cell carcinoma (BCC) and cutaneous squamous cell carcinoma (cSCC), following a dose-dependent trend 4 .…”
mentioning
confidence: 99%